Concept of an induction-dynamic catapult for a ballistic laser gravimeter - Bolyukh, V. F.; Vinnichenko, A. I. (Springer Science+Business Media New York, 2014)
A design is proposed for an inductive-dynamic catapult in a ballistic laser gravimeter with a fixed inductor and an electrically conducting armature that moves together with the test object along a vertical axis. The catapult ensures improved accuracy of the gravimeter through direct conversion of electrical into kinetic energy. The electrical circuit of the catapult provides two successive current pulses to the inductor for launching and braking of the armature during the operating cycle.
Keywords: ballistic laser gravimeter; induction-dynamic catapult; mathematical model; launching and braking of armature